1973
DOI: 10.1002/hlca.19730560723
|View full text |Cite
|
Sign up to set email alerts
|

Über den Verlauf der Umsetzung von Steroid‐3,5‐dienaminen mit Formaldehyd

Abstract: Reaction of steroidal 3,5‐dienamines (including 9β,10α‐ and 19‐nor‐compounds) with formaldehyde gave 6‐hydroxymethyl derivatives as major products. The latter compounds are valuable intermediates for the preparation of 6‐methyl‐3‐keto‐Δ4,6‐steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The 13 C NMR spectrum revealed 25 signals including four methyls, one methoxyl, eight methylene, five methines, four quaternary carbons and three carbonyls. Comparison with reported data of the known compound, 17␣-acetoxy-6␣-hydroxylmethylpregna-4-ene-3,20-dione [5], showed that impurity 3 is its methyl ether. The relative stereochemistry at C-6 was determined based on the characteristic J H-4, H-6 long-range coupling constant: for H-6 in ␣ form, the signal in H-4 must be a single peak, while H-6 in ␤ form, H-4 are generally double-peak (J in ∼1.5 Hz).…”
Section: Nomentioning
confidence: 81%
“…The 13 C NMR spectrum revealed 25 signals including four methyls, one methoxyl, eight methylene, five methines, four quaternary carbons and three carbonyls. Comparison with reported data of the known compound, 17␣-acetoxy-6␣-hydroxylmethylpregna-4-ene-3,20-dione [5], showed that impurity 3 is its methyl ether. The relative stereochemistry at C-6 was determined based on the characteristic J H-4, H-6 long-range coupling constant: for H-6 in ␣ form, the signal in H-4 must be a single peak, while H-6 in ␤ form, H-4 are generally double-peak (J in ∼1.5 Hz).…”
Section: Nomentioning
confidence: 81%
“…Although the stereochemistry at the 6-position was not assigned in the current paper, we speculate the stereo orientation for the 6 substitute is “ α ” for both synthesized 6-EXE-cys and 6-17 β -DHE-cys based on the proton coupling constant between the proton at the 4-position and the proton at the 6-position of both EXE-cys and 17 β -DHE-cys conjugates. For 6-substituted steroids, long-distance coupling between H-4 and H-6 in 1 H NMR will be observed only when the 6-substituent is in the α position ( Chin and Warren, 1972 ; Schneider et al, 1973 ; Numazawa and Oshibe, 1994 ; Numazawa and Yamaguchi, 1998 ; Görlitzer et al, 2006 ). In an analysis of a series of 6-substituted phenylaliphatic steroids, Numazawa and Yamaguchi (1998) demonstrated that proton coupling between the hydrogens at the 4- and 6-positions was only observed for the 6 α -substituted, but not the 6 β -substituted, phenylaliphatic steroids.…”
Section: Discussionmentioning
confidence: 99%